Implementation Of The Supervision System, Components Of The Supervision System And The Function Of The Supervision System For Digital-Based Supervision In The North Toraja Regency Inspectorate - Tandi, Asrin; Allo, Yohanis Tasik; Tolla, Yeni (Journal Research of Social Science, Economics, and Management, 2024)
The purpose of the study was to determine and analyze the effect of the Implementation of the Supervisory System, the Components of the Supervision System and the Function of the Supervision System on Digital-Based Supervision in the North Toraja Regency Inspectorate. This type of research is quantitative research because it emphasizes more on the aspect of objectively measuring social phenomena. The object of this research is the North Toraja Inspectorate Office of South Sulawesi Province. The population in this study is all employees of the North Toraja Inspectorate Office of South Sulawesi Province. Based on data obtained from the Personnel Section, the total number of North Toraja Inspectorate Offices is 46 employees. The sampling technique in this study uses the saturated sampling technique, where all members of the population are used as research samples, because the population is relatively small only 46 people, so the total sample in this study is 46 people who are used as respondents. The analysis method uses descriptive analysis and multiple linear regression analysis. The results showed that: 1) The implementation of the supervision system has a positive and significant effect on digital-based supervision, the better the implementation of the supervision system, the better the digital-based supervision; 2) The components of the supervision system also have a positive and significant effect on digital-based supervision, the better the components of the supervision system, the better the digital-based supervision;